STRATEGY ANALYSIS OF SOLID WASTE MANAGEMENT IN PALM OIL PROCESSING PLANT PT PERKEBUNAN NUSANTARA VII UNIT TALO PINO KECAMATAN PRING BARU KABUPATEN SELUMA - Indra Utama; Hasan Basri Daulay; Tuti Tutuarima (BPFP Faperta UNIB, 2017)
The purpose of this research is to get the strategy and the utilization of empty bunch waste, shell, and fiber waste at Plantation Processing Plant PTPN VII Unit Talo Pino. Data collection method in this research is field empirical observation method on the management of solid waste of empty bunches, shells and fibers. The results showed that the strategy of Plantation Processing Plant PTPN VII Unit Talo Pino using the principle of reuse and reduce. 100% empty bunch waste is reused for land application and distributed to 3rd parties. 100% fiber waste is used for fuel in the boiler. While shell waste is managed by reusing it for boiler surplus, PTPN VII dryer Unit Padang Pelawi and distributed to 3rd party. The management is able to save the budget for the purchase of fertilizer, fuel oil usage budget and able to increase the company's revenue.Keywords :